EYE TUMOR PATIENTS AT TUMOR DIVISION EYE CLINIC SANGLAH GENERAL HOSPITAL BALI-INDONESIA - Yuliawati, P.; Piliantari-Meigawati, and N. L. (BALI MEDICAL JOURNAL, 2013)
Objective: Tumors in the eye are type of tumors that could afflict eyeball and adnexa. Even though, the incidence is rare, these tumors that usually are secondary tumors cause by cancer spread from other parts of the body, especially the breast, lung, bowel or prostate. Two types of primary tumors arise within the eye itself are known as retinoblastoma in children and melanoma in adults. This study aims to obtain basic figure of eye tumor patients at Sanglah General Hospital Bali-Indonesia, in which these data can be used as a reference for further research. Methods: Descriptive and retrospective methods were applied to observe the patient who came during the period of 1 January 2005 until 30 September 2010. The numbers were taken from the medical records. Results: There were 44 patients recruited, consisting of 59.1% male and 40.9% female. A number of 29.5% of them are between 61-70 years old, 34.1% are from Denpasar, and 34.1% are farmers. There were 95.5% of the patients suffered from an eye lump, and 40.9% of them came with 0.00 logMar of visual acuity. About 47.7% of the tumor grew in the superior palpebra. Pathology anatomy test shows 20.5% Squamous Cell Carcinoma (SCC), 11.4% Basal Cell Carcinoma (BCC), and 11.4% papilloma. Conclusions: The patients at tumor division, eye clinic of Sanglah General Hospital were mostly male, with major age range of 61-70 years old that mainly live in Denpasar as farmers. Their major complaint was the eye lump, which mainly found in the superior palpebra. The pathology anatomy result shows that SCC and BCC was the top and second most found illness. This study can be used as a reference for future research.